Vertical flexibility, outsourcing and the financial choices of the firm - Michele Moretto; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
We investigate the relationship between the extent of vertical flexibility and the underlying financial choices of a firm. By vertical flexibility we mean the opportunity to outsource a necessary input and to reverse the choice as input market conditions dictate. A firm simultaneously selects the portion of equity and debt and its vertical setting. Debt is provided by a lender that requires the payment of a fixed coupon over time and, as a collateral, an option to buy out the firm in certain circumstances. Debt leads to the same level of flexibility acquired by an unlevered firm. However, investment to set up a flexible technology occurs earlier. An alternative to debt is the involvement of venture capital for the production of the input. We explore this second avenue finding that the extent of outsourcing adopted is lower than for the unlevered firm, but the firm invests earlier.
Keywords: C61; G31; G32; L24; 330